(untitled) - Eccleston, Charles H. (New York, 2000)
An Environmental Impact Statement (EIS) is a report that is required for any proposed project that has the potential to result in significant impacts on the environment. If it is a privately funded project, such as a new factory or other large construction project, an EIS needs to be filed. This is the most practical guide available on EIS preparation, while also presenting a solid working strategy for any large-scale project that gets the work done efficiently and effectively.